2016
DOI: 10.18805/ijar.11158
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of reproductive traits in Jersey crossbred heifersat an organized farm of eastern India

Abstract: The present study was conducted on data of reproductive traits (viz., age at first service and age at first calving) in Jersey crossbred heifers, maintained at the Eastern Regional Station of ICAR-National Dairy Research Institute, Kalyani, West Bengal over a period of 38 years to determine the effects of genetic and non-genetic factors. The data were classified according to season of birth, period of birth of animals and distributed in eight genetic groups having different level of Jersey inheritance. The le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In accordance with our findings, Chaudhari ( 8 ) recorded medium heritability for FSP and FCI in Nili-Ravi. Medium heritability for AFC was reported by Kumar et al ( 13 ) in Murrah, Singh and Yadav ( 14 ) in Nili-Ravi, and Kumar et al ( 15 ) in cattle. In contrast, high heritability was observed for the FLTMY and FLSMY in Nili-Ravi ( 3 ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In accordance with our findings, Chaudhari ( 8 ) recorded medium heritability for FSP and FCI in Nili-Ravi. Medium heritability for AFC was reported by Kumar et al ( 13 ) in Murrah, Singh and Yadav ( 14 ) in Nili-Ravi, and Kumar et al ( 15 ) in cattle. In contrast, high heritability was observed for the FLTMY and FLSMY in Nili-Ravi ( 3 ).…”
Section: Discussionmentioning
confidence: 77%
“…in Murrah,Singh and Yadav (14) in Nili-Ravi, and Kumar et al(15) in cattle. In contrast, high heritability was observed for the FLTMY and FLSMY in Nili-Ravi (3).…”
mentioning
confidence: 95%
“…In contrast, Kumar et al. (2016) illustrated a wider range of heritability (0.04 to 0.10) and maternal effects (0.06 to 0.09), highlighting the diverse genetic nature of SP across different cattle populations. Radwan et al.…”
Section: Discussionmentioning
confidence: 89%
“…Comparing our findings with the breadth of existing research, Kumar and Mandal's (2021) study on Jersey crossbred cows reported a higher heritability ranging from 0.14 to 0.20 and a similar maternal effect (m 2 = 0.00 to 0.02), emphasizing the shared genetic influences but with higher heritability in their study. In contrast, Kumar et al (2016) illustrated a wider range of heritability (0.04 to 0.10) and maternal effects (0.06 to 0.09), highlighting the diverse genetic nature of SP across different cattle populations. Radwan et al (2017) explored SP in Holstein cattle, revealing a higher heritability (0.49 to 0.233) and substantial additive genetic variance (2226.61 to 3275.48), signifying breed-specific complexities.…”
Section: Inmentioning
confidence: 97%
“…Lower than the present finding has been reported by Narwaria et al (2015) and Wakchaure and Meena (2010) in Sahiwal cows being 1136.14 ± 10.48 days and 1078.09 ± 21.12 days, respectively. Kumar et al (2017) studied in Jersey crossbred heifers and found 1089.36 ± 13.99 days of age at first calving with the coefficient of variation 14.27%. A relatively higher value for age at first calving was reported by Rehman et al (2008) in Sahiwal cows (1390 ± 3.9 days) and Moulick et al (1972) in Deshi cows (44.5 ± 6.8 months).…”
Section: Age At First Calvingmentioning
confidence: 99%